Modelling tourism demand from United Kingdom to Maldives: a cointegration analysis - Auzar, Hussain; Mhd Bani, Nor Yasmin; Ishak, Suryati (Penerbit Universiti Malaysia Terengganu, 2020)
Maldives depends heavily on tourism industry. According to 2016 Tourism Yearbook, the demand for international tourism remains robust despite political and economic conflicts around the world. In 2015, tourist arrivals grew at a pace of 4% exceeding the long-term average (3.8%) for the sixth consecutive years (Ministry of Tourism, Maldives, 2016). Europe has been one of the major market generators for Maldives tourism since 1990’s. At the end of 2015, United Kingdom was the third largest market with 7.5% market share behind Germany and China. The aim of this paper is to examine the short run and long run demand for tourism to Maldives by United Kingdom. Using quarterly data from 2006Q1 to 2016Q4, the paper examines the significance of the Gross Domestic Product (GDP) of United Kingdom, tourism price and cost, as well as exchange rate in determining the important factors for tourist arrivals. The paper employs a cointegration approach that is the bounds testing approach within the ARDL framework which has been used previously in tourism demand model. The findings are consistent with the theory and existing literature whereby income, tourism price and transportation cost are important determinants for tourism demand in Maldives.